EARLY SUCCESSFUL PRIMARY PERCUTANEOUS CORONARY INTERVENTION ON LEFT VENTRICULAR EJECTION FRACTION IN PATIENTS WITH ST-ELEVATION MYOCARDIAL INFARCTION - JAN , MT; KHAN, MA; NOMAN, M; ULLAH, H; ALAM, K; RIAZ, M; HAQ, IU; AFZAL, S (Biological and Clinical Sciences Research Journal, 2024)
Early intervention in patients with ST-elevation myocardial infarction (STEMI) is crucial for preserving left ventricular function and improving patient outcomes. Primary percutaneous coronary intervention (PPCI) has become the standard of care, and the timing of intervention significantly influences recovery and long-term prognosis. Objective: This study aimed to evaluate the impact of early successful primary percutaneous coronary intervention (PPCI) on left ventricular ejection fraction (LVEF) in patients presenting with STEMI. Methods: A prospective cohort study was conducted on 116 STEMI patients undergoing PPCI at a tertiary care hospital. The patients were categorized into two cohorts: early presenters (n=67) who received PPCI within 6 hours of symptom onset and late presenters (n=49) who received PPCI after 6 hours. Baseline characteristics, procedural outcomes, Thrombolysis in Myocardial Infarction (TIMI) flow grades, and LVEF measurements were assessed at presentation and two months post-PPCI using transthoracic echocardiography. The primary outcome was the change in LVEF from baseline to follow-up, and the secondary outcome was the distribution of TIMI flow grades achieved during PPCI. Statistical analysis was performed using appropriate tests to compare outcomes between the two groups. Results: Early presenters demonstrated significantly better outcomes compared to late presenters. At presentation, the mean LVEF in the early group was higher (45.67 ± 1.73%) compared to the late group (36.94 ± 1.25%) (p = 0.0001). At the two-month follow-up, the LVEF improved significantly in both groups, with early presenters achieving an LVEF of 56.24 ± 1.73%, which was notably higher than the LVEF of late presenters (45.12 ± 1.42%) (p = 0.0001). In terms of coronary reperfusion, 62.7% of early presenters achieved TIMI grade 3 flow compared to 26.5% of late presenters (p = 0.0001), indicating better coronary artery perfusion in the early intervention group. Conclusion: Early successful PPCI in STEMI patients is associated with superior recovery of left ventricular function and improved coronary reperfusion compared to delayed intervention. Patients who received PPCI within 6 hours of symptom onset demonstrated significantly higher LVEF at follow-up and achieved better TIMI flow grades, highlighting the critical importance of minimizing treatment delays in STEMI management.